TO EXPLORE THE RELATIONSHIP BETWEEN ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND JOB PERFORMANCE, WITH JOB SATISFACTION AS THE MEDIATING VARIABLE - Linda Lin Chin Lin; Ping Kuei Tsao; Tsu Ning Huang; Chun Ning Hu (Graduate Program of Universitas Tarumanagara, 2025)
In today’s business environment, companies face expectations and pressures from various stakeholders, with employees being the most important. Attracting employees and establishing interaction with them is a key factor in creating a competitive advantage for the business. Employee engagement with the company is typically influenced by their attitudes and feelings toward the organization. Employees' pride in the company will stem from their positive perceptions of the business and its achievements. As a result, they will put more effort into contributing to the business and demonstrate greater loyalty to the company. In today’s Taiwan, the post-pandemic era and the trend of declining birth rates have put significant pressure on companies that focus on human resource services. As a result, employee organizational citizenship behavior and job performance have become increasingly important topics for businesses. This study aims to explore the relationship between organizational citizenship behavior (OCB) and employee job performance, and further examine the mediating role of job satisfaction in this relationship. As a voluntary behavior that goes beyond job responsibilities, OCB has a profound impact on organizational operations, while employee job performance is an important indicator of employee contributions. Previous studies have primarily focused on the direct relationship between OCB and employee job performance. However, job satisfaction, as a potential mediating variable, has not been sufficiently explored. This study uses a questionnaire survey method to collect data from employees in various service industries and employs SPSS statistical analysis to examine the mediating effect of job satisfaction on the relationship between OCB and employee job performance. The results show that OCB has a positive impact on employee job performance, with job satisfaction playing an important mediating role. Specifically, when employees exhibit higher levels of OCB at work, it enhances their job satisfaction, which in turn boosts their job performance. The results of this study not only enrich the theoretical foundation between OCB and employee job performance, but also highlight the importance of job satisfaction in this relationship, providing practical recommendations for businesses in human resource management. Future research could further explore other potential mediating variables, as well as the differences in OCB and employee job performance across different cultural contexts.